2019
DOI: 10.1002/wcs.1517
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic context effects in speech perception

Abstract: The extreme acoustic variability of speech is well established, which makes the proficiency of human speech perception all the more impressive. Speech perception, like perception in any modality, is relative to context, and this provides a means to normalize the acoustic variability in the speech signal. Acoustic context effects in speech perception have been widely documented, but a clear understanding of how these effects relate to each other across stimuli, timescales, and acoustic domains is lacking. Here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 163 publications
(252 reference statements)
0
26
0
Order By: Relevance
“…This acoustic context effect induced by the surrounding speech rate, known as a temporal contrast effect or rate normalization, has been shown to influence a wide range of different duration-based phonological cues such as voice onset time (VOT; 11,12 ), formant transition duration 13 , vowel duration 14,15 , lexical stress 16 , and word segmentation 17,18 . In fact, a similar contrastive effect is found in the spectral domain: a sentence with a relatively low first formant (F1) can bias the perception of a following target with an ambiguous F1 (e.g., ambiguous between "bit" and "bet") towards a high F1 percept ("bet"; known as a spectral contrast effect or spectral normalization 6,19,20 ).…”
Section: Temporal Contrast Effects In Human Speech Perception Are Immmentioning
confidence: 84%
“…This acoustic context effect induced by the surrounding speech rate, known as a temporal contrast effect or rate normalization, has been shown to influence a wide range of different duration-based phonological cues such as voice onset time (VOT; 11,12 ), formant transition duration 13 , vowel duration 14,15 , lexical stress 16 , and word segmentation 17,18 . In fact, a similar contrastive effect is found in the spectral domain: a sentence with a relatively low first formant (F1) can bias the perception of a following target with an ambiguous F1 (e.g., ambiguous between "bit" and "bet") towards a high F1 percept ("bet"; known as a spectral contrast effect or spectral normalization 6,19,20 ).…”
Section: Temporal Contrast Effects In Human Speech Perception Are Immmentioning
confidence: 84%
“…The challenge of rampant stimulus variability is lessened by emphasizing differences between stimuli, which highlights new information that can inform adaptive behavior (Kluender & Alexander, 2007). Perception of speech and nonspeech sounds is widely influenced by spectral contrast effects (SCEs; e.g., Christman, 1954;Kingston et al, 2014;Ladefoged & Broadbent, 1957;Stilp et al, 2010;Stilp et al, 2015; for reviews, see Kluender et al, 2003;Stilp, 2019b). These demonstrations generally used highly acoustically controlled stimuli, which affords good experimental control, but does not necessarily model the acoustic variability present in everyday perception.…”
Section: Discussionmentioning
confidence: 99%
“…For example, when context sounds are spectrally similar to /o/ (higher frequency first formant), listeners are more likely to categorize the subsequent target vowel as /u/ (lower frequency first formant) and vice versa. SCEs have been repeatedly shown to influence speech perception (e.g., Holt, 2006;Ladefoged & Broadbent, 1957;Sjerps, Zhang, & Peng, 2018;Stilp, 2019b;Stilp, Anderson, & Winn, 2015;Watkins, 1991). This influence extends to perception of other complex sounds such as musical instruments (Stilp, Alexander, Kiefte, & Kluender, 2010).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Many experimental studies have found that words in the context of the sentence have been identified better than words in isolation. For a detailed discussion on the subject see, among others, Mullennix & Pisoni (2014) or Stilp (2019). "l'I me paroissoit toujours beaucoup plus aigu que l'O ou l'OU" (p. 407).…”
mentioning
confidence: 99%